2016
DOI: 10.1016/j.plefa.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and tolerance of infants fed formula with a new algal source of docosahexaenoic acid: Double-blind, randomized, controlled trial

Abstract: Docosahexaenoic acid (DHA) in infant formula at concentrations based on worldwide human milk has resulted in circulating red blood cell (RBC) lipids related to visual and cognitive development. In this study, infants received study formula (17mg DHA/100kcal) with a commercially-available (Control: n=140; DHASCO®) or alternative (DHASCO®-B: n=127) DHA single cell oil from 14 to 120 days of age. No significant group differences were detected for growth rates by gender through 120 days of age. Blood fatty acids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…A majority of infants in all groups were reported to have a soft (Category 3) stool consistency at day 120 with no significant differences among study formula groups and few differences observed for the PDX/GOS group at day 30 only. We have previously demonstrated a prebiotic blend of PDX and GOS was well-tolerated, supported normal growth, promoted softer stools [21,22,27,46], closer to that of breastfed infants [23,47], and a bifidogenic effect closer to breast milk when compared to infants fed a formula without the prebiotic blend [23]. Stool consistencies in the current study were consistent with previous studies in infants receiving a prebiotic blend of PDX and GOS in infant formulas.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A majority of infants in all groups were reported to have a soft (Category 3) stool consistency at day 120 with no significant differences among study formula groups and few differences observed for the PDX/GOS group at day 30 only. We have previously demonstrated a prebiotic blend of PDX and GOS was well-tolerated, supported normal growth, promoted softer stools [21,22,27,46], closer to that of breastfed infants [23,47], and a bifidogenic effect closer to breast milk when compared to infants fed a formula without the prebiotic blend [23]. Stool consistencies in the current study were consistent with previous studies in infants receiving a prebiotic blend of PDX and GOS in infant formulas.…”
Section: Discussionsupporting
confidence: 88%
“…Study feeding through 120 days of age would be a sufficient length to reflect the neonatal RBC lifespan of 60-80 days and fatty acid remodeling over that period [25,26]. We previously reported a similar approach to establish equivalence with respect to DHA in formulas for infants by evaluating total RBC DHA concentrations (µg/ml) [27].…”
Section: Study Objectives and Outcomesmentioning
confidence: 99%
“…Good Manufacturing Practice guidelines are provided by the US Food and Drug Administration to insure that an infant formula meets the quality factor of normal physical growth [15,16]. Consequently, the current multicenter, double-blind, randomized, controlled, parallel-group, prospective trial is similar in design to previously reported studies [17,18] in order to report consistent growth outcomes across different study cohorts. The research protocol and informed consent forms observing the Declaration of Helsinki (including October 1996 amendment) were approved by: the University of Louisville Institutional Review Board (IRB; Louisville, KY); the University of Nebraska Medical Center IRB (Omaha, NE); Western IRB (Olympia, WA); and Schulman IRB (now known as Advarra, Columbia, MD).…”
Section: Methodsmentioning
confidence: 99%
“…At all study visits parents completed a 24-h recall of tolerance (fussiness and gassiness) and stool characteristics (frequency and consistency); study formula intake (fluid oz./day) was reported beginning at the 30 days of age visit. We have previously characterized tolerance using the same reporting scales [17,18,19,20,21]Although parental recall may vary among individuals, participant randomization ensures balance between study groups. Responses were scaled for amount of gas (none = 0, slight amount = 1, moderate amount = 2, excessive amount = 3); fussiness (not fussy = 0, slightly fussy = 1, moderately fussy = 2, very fussy = 3, extremely fussy = 4); and stool consistency (hard = 1, formed = 2, soft = 3, unformed or seedy, watery = 4).…”
Section: Study Objectives and Outcomesmentioning
confidence: 99%
“…Similarly to Yeiser at al. ([ 90 ]), a computer-generated randomization schedule was prepared and inserted into sealed envelopes that were consecutively-numbered. The individual study formulas were designated using one of two unique codes.…”
Section: Methodsmentioning
confidence: 99%